Somatic symptom presentations in women with fibromyalgia are differentially associated with elevated depression and anxiety - Hadlandsmyth, Katherine (J Health Psychol, 2017)
This study examined whether depression and anxiety differentially relate to fatigue, sleep disturbance, pain catastrophizing, fear of movement, and pain severity in women with fibromyalgia. Baseline data from the Fibromyalgia Activity Study with TENS (FAST) were analyzed. Of 191 participants, 50% reported high anxiety and/or depression (17% high anxiety, 9% high depression, and 24% both). Fatigue and sleep impairment were associated with high depression (p < .05). Pain severity, pain catastrophizing, and fear of movement were associated with high anxiety and high depression (p < .05). Possible implications for underlying mechanisms and the need for targeted treatments are discussed.